The Influence of Organizational Justice, Grit and Leader-Member Exchange on Employee Engagement - Eledora, Astrid Octina; Utomo, Kabul Wahyu; Sultan, Zulkifli; Yusriani, Sri (Yayasan Sinergi Kawula Muda, 2024)
The purpose of this paper is to determine the influence of organizational justice, grit, and leader-member exchange on employee engagement. This research is quantitative research using survey questionnaire prepared on a five-point Likert scale. Proportionate stratified random sampling was used to select the state civil servants from the head office of the Ministry of Education, Culture, Research and Technology (MOECRT) that was located in Senayan, Jakarta. A total of 340 questionnaires were distributed and 243 valid responses collected. Data were analyzed using the structural equation modelling with the help of SmartPLS 4 software. It was found that organizational justice, grit, and leader-member exchange had a positive and significant impact on employee engagement. MOECRT shall focus on the practice of organizational justice in building high quality leader-member exchange and developing grit trait within the employee as they have positive impact on employee engagement.